Fernández Cortés, P. (2018). El centro Bohemio Occidental (1892–1916). Orígenes de sus vínculos, sociabilidades y estética. Universidad de Guadalajara. 393 pp. - Hernández Larios, Julieta (Letras Históricas E-ISSN: 2448-8372, 2020)
Reseña de libro.